Evaluating the Tax Management Practices of Selected Construction Enterprises in Yubei District, Chongqing, China - Zhu, Ling (JPAIR Multidisciplinary Research, 2025)
This study evaluates the tax management practices of selected construction enterprises in the Yubei District, Chongqing, China. Through a quantitative-descriptive research method, this study obtained 385 responses from five construction companies in the district, revealing significant trends in the construction sector.  The demographic data indicates that a majority of employees work for relatively young firms, with 60.3% employed at companies operating for 10 years or less. Additionally, a significant portion of the workforce is associated with firms reporting lower net profits, as 62.6% earn less than CN¥200,000. The evaluation of tax management practices reveals a general indication of manifestation to a great extent of such practices among respondents regarding their companies' transparency and fairness in pricing, contract planning, subcontracting methods, labor costs, and enterprise planning. Statistical analyses, including the Kruskal-Wallis test, highlight significant evaluation differences based on years of operation, net profit, employee experience, and job position. Established firms (over 20 years) received higher ratings in reasonable pricing and contract planning than newer ones. Similarly, employees with more experience rated tax management practices more favorably. Notably, executive-level respondents consistently provided higher evaluations across various tax management practices, indicating a correlation between job position and evaluation of tax management effectiveness. The findings underscore the importance of experience and company maturity in shaping evaluation of tax management practices. Furthermore, the study suggests that higher-profit companies tend to employ more sophisticated tax strategies, while smaller firms may struggle with efficiency.
Keywords: tax management; practices; construction enterprises; descriptive research; Chonqing; China